KUALITAS PELAYANAN ADMINISTRASI PENSIUN BADAN KEPEGAWAIAN DAERAH PROVINSI SULAWESI TENGAH - Lobud, Wiwiyanti; Daswati, Daswati; Mansur, Sastrio (Katalogis, 2020)
The formulation of the problem in this study is how the quality of pension administration services in the central sulawesi provincial civil service agency. This research was analyzed descriptively qualitatively. As for the informants in this study were the head of the mutatin departement, the head of the pension sub sector, 2 (two) pension administration management staff and 4 (four) candidates who had received pension administration services carried out by purposive sampling technique. Data colection and retrieval techniques consist of observation, interviews and documentation. The theory used to determine the quality of pension administration services is the theory of parasuraman, zeithaml and berry wich consists of tangibles, reliability, responsiveness, assurance, empathy.The result of the study show that the quality of pension administration services in the central sulwesi provincial personnel aggency in terms of reliability, responsiveness, assurance and emphaty show a good level of service quality because of all these aspects there is nothing to hinderquality of pension administration services so as to make prospective retirees well served and qualified.Whereas in the tangibles aspect there are problems with inadequate supoporting facilities and infrastructure, such as the avaliability of poorly functioning air conditioners, inadequate toilets, irregular parking areas and less extensiveservice spaces that provide inconveniencefor prospective retirees.